Long-term follow-up of planned treatment of spontaneous pneumothorax - Lichter, Ivan (1974)
Lichter, I. (1974).Thorax, 29, 32-37. Long-term follow-up of planned treatment of spontaneous pneumothorax. Ninety-six patients presenting with spontaneous pneumothorax have been followed for a period of five to 12 years after initial treatment. Treatment was designed to deal with the pneumothorax episode and management was planned to minimize the risk of recurrence. Patients were treated initially by intercostal tube drainage, and subsequent management depended upon the nature of the underlying disease and the behaviour of the pneumothorax. Two groups of patients were identified. Group A were young fit subjects with disease confined to the apex of the lung. Group B were older subjects with overt, often widespread pulmonary disease. In the first group of young fit patients, early wedge resection was advised for patients at greatest risk of recurrence—those who had suffered a previous pneumothorax and those in whom the leak had persisted for more than 48 hours. Limited wedge resection removes the whole of the diseased tissue, leaves normal lung uncompromised, and is uniformly successful. In the group of older patients, extensive disease precludes the use of the same safe and effective treatment. For this reason tube drainage was frequently continued for up to 14 days. Failure of treatment by tube drainage was treated by excision of bullae in those patients who were fit for thoracotomy, and by pleurodesis in the remainder. Intercostal tube drainage alone was successful in 77% of group A patients and in 52·5% of group B patients so treated. With planned management as recommended, 95% of group A and 87% of group B patients were either cured by tube drainage alone or treated definitively and lastingly during their first admission to hospital.